Language processing and simultaneous interpreting : interdisciplinary perspectives - Englund Dimitrova, Birgitta, 1946-; Hyltenstam, Kenneth (Benjamins translation library, 2000)
This volume brings together papers from the areas of psychology, general linguistics, psycholinguistics, as well as from simultaneous interpreting. Their common focus is how theories and methodologies from various disciplines can be applied to the study of simultaneous interpreting, and also to suggest ways in which the study of simultaneous interpreting in its turn might contribute to knowledge in other areas. General topics dealt with include memory, language processing, bilingual processing, and second language acquisition. The articles more specifically focused on simultaneous interpreting.